Efeitos agudos de flunitrazepam sobre o metabolismo da homocisteína em jovens saudáveis - Grego, Bruno Henrique do Carmo [UNIFESP] (2009)
Background: High cortisol plasma concentrations have been shown to be associated with increases in homocysteine. Here we studied whether decreases in cortisol, induced by an acute oral dose of a benzodiazepine, could decrease homocysteine, and if changes were similar in both genders. Methods: This was a double-blind, cross-over design study of acute oral doses of flunitrazepam and placebo in young, healthy, male and female volunteers. Blood samples were collected after peak-plasma concentration of flunitrazepam. Various biochemical parameters were analysed, such as homocysteine, cysteine, folate, vitamins B6 and B12, as well as male and female hormones. Results: flunitrazepam reduced cortisol, cysteine and homocysteine plasma concentrations, irrespective of gender. No correlations were found between cortisol and other biochemical markers. Plasma concentration of cysteine and homocysteine were negatively correlated with plasma flunitrazepam concentration, suggesting that changes in these amino acids were related to the metabolism of this benzodiazepine. Conclusion: Acute administration of flunitrazepam decreases plasma homocysteine and cysteine through as yet unknown mechanisms that do not seem related to changes in cortisol. Given the importance of homocysteine as a marker of life-threatening disorders, such mechanisms are potential targets for clinical application.